LATIHAN MANAJEMEN PENGOLAHAN SAMPAH BAGI MASYARAKAT KELURAHAN CEMPAKA PUTIH TIMUR, JAKARTA [WASTE MANAGEMENT TRAINING FOR CEMPAKA PUTIH TIMUR VILLAGE, JAKARTA] - Katherine Kho; Solmaz Aslanzadeh; Siti Muslimatun; Putu Virgina Partha Devanthi (Jurnal Sinergitas PKM & CSR, 2019)
DKI Jakarta is currently in a state of waste emergency because Bantar Gebang landfill is estimated to reach its full capacity by 2021. This problem should not be solely solved by the city’s administrator but must also involve all citizens. As one of the efforts to contribute to the solution, training was given to representatives from RW 1 – 4 in Cempaka Putih Timur village. These representatives consist of community groups (RW) leaders, neighborhood groups (RT) leaders, and environmentalist. The goal of the training was to educate the representatives on how to manage waste properly, starting from reducing waste until the method of handling waste before it is disposed of. The final goal is to apply the content of the training in the village and reduce the amount of waste delivered to Bantar Gebang landfill. The approach used in the training was student – centered learning to improve the participants’ understanding. The activity was started with a discussion, followed by sharing of waste management method, followed by games for deeper understanding. The analysis of the result of the training, analyzed by the difference in pre – game and post game’s score and survey to the trainees, indicates an increased understanding of the participants.